(3OQGSI ebGQfIs - (3YdGA eMj GdOjf eUWai(B, (3CHh CMeOs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2008)
(3GdHGH GdChd (B: (3GdYbhO GdGOGQjI GdOhdjI eGgjI GdYbhO GdGOGQjI GdOhdjI , CWQGa GdYbhO GdGOGQjI GdOhdjI , Jcja GdYbhO GdeHQeI Hjf LgI GdOGQI hGdeSJKeQ GdCLfHj , GHQGe GdYbhO GdGOGQjI GdOhdjI , CKGQ GdYbhO GdGOGQjI GdOhdjI GdHGH GdKGfj (B: (3GJaGb GdJMcje GdOhdj aj GdYbhO GdGOGQjI eOi GecGfjI GdJaGb Ydi GdJMcje aj GdYbhO GdGOGQjI GdOhdjI , GSJbdGd GJaGb GdJMcje aj GdYbhO GdGOGQjI GdOhdjI , TQhW UMI GJaGb GdJMcje , GJaGb GdJMcje GdHGH GdKGdK (B: (3GddLhA Edi GdJMcje aj GdYbhO GdGOQjI GdOhdjI GdbGfhf GdhGLH GdJWHjb Ydi GdYbhO GdGOGQjI GdOhdjI , UOhQ Mce GdJMcje heOi GecGfjI GdWYf YdjI , JfajP CMcGe GdJMcjes
(3HjHdjhZQGajG(B: (3U(B.473 -495s
Keywords: (3GdJMcjes; (3GdYbhO GdGOGQjIs; (3GdbGfhf GdOhdjs; (3GdeaGhVGJ GdOhdjIs; (3GdefGRYGJs